Sinergi Sivitas Akademika Politeknik Kutaraja Dalam Respon Bencana Banjir dan Distribusi Bantuan Berbasis Masyarakat - Desy Puspita; Zahriatul Aini; Azlina Azlina; Mirnawati Mirnawati; Agustina Agustina; Khairita Hasbi; Cut Intan Amalia; Suprihatin Ningsih; Vicky Rahmat; Zakiyul Fata; Aidil Akbar; M. Eriq Akbar; Raihul Miski; Ghuzzyian Al Sidqi (PELITA NUSA TENGGARA, 2026)
This Community Service Program (PkM) aims to strengthen the role of the academic community of Politeknik Kutaraja in emergency response to flood disasters and the distribution of community-based social assistance in Dayah Husein Village, Meurah Dua District, Pidie Jaya Regency. The flood disaster that struck several areas in Aceh at the end of 2025 caused significant social and economic impacts, particularly for communities in areas that had not been optimally reached by aid. The program was implemented through fundraising activities, coordination with local volunteers, community needs assessment, and direct distribution of social assistance to affected residents. The results indicate that synergy between lecturers, students, local communities, and volunteers significantly improved the effectiveness and accuracy of aid distribution. The humanitarian assistance provided included food supplies, basic necessities, and essential items for vulnerable groups. This activity not only delivered direct benefits to flood-affected communities but also strengthened social awareness, humanitarian solidarity, and the strategic role of vocational higher education institutions in community-based disaster management. This program is expected to serve as a collaborative model between universities and communities in sustainable disaster response initiatives.